Synthesis of Functionalized Magnetite Titanium Dioxide Nanocomposite for Removal of Acid Fuchsine Dye - Rahnama, Sara; Shariati, Shahab; Divsar, Faten (Combinatorial Chemistry & High Throughput Screening, 2018)
Objective: In this research, a novel magnetite titanium dioxide nanocomposite functionalized by amine groups (Fe3O4@SiO2@TiO2-NH2) was synthesized and its ability for efficient removal of Acid Fuchsine as an anionic dye from aqueous solutions was investigated. Method: The core-shell structure of Fe3O4@SiO2@TiO2 was prepared using Fe3O4 as magnetic core, tetra ethyl orthosilicate as silica and tetra butyl titanate as titanium source for shell. The synthesized nanocomposites (particle size lower than 44 nm) were characterized by FT-IR, XRD, DRS, SEM and TGA instruments. The various experimental parameters affecting dye removal efficiency were investigated and optimized using Taguchi fractional factorial design. Results: The synthesized adsorbent showed the highest removal efficiency of Acid Fuchsine (99 %) at pH= 3.5, without salt addition and during stirring at contact times less than 10 minutes. The study of kinetic models at two concentration levels showed the fast dye sorption on the surface of proposed nanocomposites with pseudo second order kinetic model (R2=1). Also, the fitting of Acid Fuchsine sorption data to Freundlich, Langmuir and Temkin isotherms suggested that Freundlich model gave a better fitting than other models (R2=0.9936, n=2). Conclusion: Good chemical stability, excellent magnetic properties, very fast adsorption kinetics and high removal efficiency make the synthesized nanocomposite as a proper recoverable sorbent for removal of Acid Fuchsine dye from wastewaters.
Keywords: titanium dioxide